Effect of eplerenone on markers of bone turnover in patients with primary hyperparathyroidism: the randomized, placebo-controlled EPATH trial - Verheyen, Nicolas; März, Winfried (Bone, 2017)
Mineralocorticoid receptor (MR) antagonism may affect bone turnover via direct and indirect pathways involving parathyroid hormone, but randomized controlled trials are lacking. In a pre-specified analysis of the “Eplerenone in primary hyperparathyroidism” placebo-controlled, randomized trial (ISRCTN 33941607), effects of eight weeks MR-blockade with eplerenone on bone turnover markers in 97 patients with primary hyperparathyroidism were tested. Mean age was 67.5±9.5years, and 76 (78.4%) were females. In analysis of covariance with adjustment for baseline values, eplerenone had no significant effect on isoform 5b of the tartrate-resistant acid phosphatase (TRAP), beta-crosslaps, N-terminal propeptide of procollagen type 1 (P1NP), osteocalcin and bone-specific alkaline phosphatase. There was no significant cross-sectional correlation between plasma aldosterone concentration or the aldosterone-to-renin ratio and markers of bone turnover in multivariate linear regression models at baseline. These data provide first evidence from a randomized and placebo-controlled trial that short-term MR antagonism may not affect bone turnover, at least in patients with primary hyperparathyroidism.